How Moroccan Film Destination Attracts More Tourists - ALHADDAR, M’barek; KUMMITHA, Harshavardhan Reddy (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023DO - 10.14505/jemt.v14.8(72).01, 2023)
With the different types of crises that the world was suffering from, management of a destination becomes more difficult than before, especially to develop the destination image. Many destinations are trying different ways to market their destinations, and one of those is the film industry. Film travel is considered a new fashion in visiting Morocco, and Essaouira is an attractive and sustainable destination. Motivating tourists to follow up the trend of travel with the film the DMO should use new ways of marketing, including sustainable projects, and taking care of the tourists’ perspectives. Several studies have confirmed the importance of film tourism in the destination image. The main objective of this study is to create a general process that can be used for any destination to make it an attractive and sustainable destination and to discover the importance of the film industry as a new way to market a destination and develop its image. Essaouira is the destination chosen for this study. Different research methods were used, an offline and online questionnaire with tourists and locals about their perspectives. Research findings indicate that film tourism is a very important tool nowadays to promote a destination and will be very helpful to use it in the case of Essaouira. It is found that a lot of people got inspired by movies to travel, and in the case of this city, it is shown that film tourism along with sustainable tourism could improve the destination's reputation and affect the tourism sector positively.